School Principal Leadership and Sustainable Governance: A Systematic Review of International Practices - Rachmadio, R. Edy; Joko; Lastriyani, Indri; Nugraha, Derry (Indonesian Scientific Publication, 2024)
This study examines the role of school principal leadership in sustainable school governance through a comprehensive multi-national literature review. The research analyzes leadership practices, challenges, and success factors across different cultural and economic contexts to identify universal principles and context-specific elements of effective school governance. Using a systematic literature review methodology following PRISMA guidelines, the study reviewed peer-reviewed articles, books, and official reports published between 2014 and 2024 from major academic databases. The findings reveal five key themes: leadership characteristics and competencies, contextual adaptations, sustainable governance practices, challenges and solutions, and the impact of external factors. Results indicate that successful sustainable school governance requires principals to balance universal leadership principles with local contextual adaptations while developing strong digital leadership capabilities and stakeholder engagement skills. The study contributes to educational leadership theory and practice by providing evidence-based insights for leadership development programs and policy formation. Furthermore, it highlights the evolving nature of school leadership challenges in the post-pandemic era and the importance of adaptive leadership approaches.